2013
DOI: 10.1108/07363761311290821
|View full text |Cite
|
Sign up to set email alerts
|

Social persuasion: targeting social identities through social influencers

Abstract: Purpose-Buying behaviour can be interpreted as a signal of social identity. For example, individuals may purchase specific cars to indicate their social status and income, or they may dress in particular ways to show their taste in fashion or their membership in a social group. This paper aims to focus on the identification of market place influencers in a social identity context, in order to better market products and services to social groups. Design/methodology/approach-A structural model linking consumers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 103 publications
(93 reference statements)
0
26
0
1
Order By: Relevance
“…Moreover, search engine ranking, content quality (Gillin, 2008) as well as brand fit and tone of voice play an essential role in selecting social media influencers for commercial purposes (Uzunoğlu & Kip, 2014). Furthermore, they are seen as influential due to their expertise in a specific field (Langner, Hennigs, & Wiedmann, 2013). Social media influencers are described as "new type of independent third party endorser who shape audience attitudes through blogs, tweets, and the use of other social media" (Freberg, Graham, McGaughey, & Freberg, 2011, p. 1).…”
Section: Youtube and Influencer Marketingmentioning
confidence: 99%
“…Moreover, search engine ranking, content quality (Gillin, 2008) as well as brand fit and tone of voice play an essential role in selecting social media influencers for commercial purposes (Uzunoğlu & Kip, 2014). Furthermore, they are seen as influential due to their expertise in a specific field (Langner, Hennigs, & Wiedmann, 2013). Social media influencers are described as "new type of independent third party endorser who shape audience attitudes through blogs, tweets, and the use of other social media" (Freberg, Graham, McGaughey, & Freberg, 2011, p. 1).…”
Section: Youtube and Influencer Marketingmentioning
confidence: 99%
“…Accordingly, we anticipate that this form of content will be a particularly strong influencer in this pre-purchase phase. Research related to other types of social video content and the content creators have also revealed that social video content creators have a strong influence on their audiences and their consumer behaviour [7,18,23].…”
Section: Previous Research and Consumer Behaviour 221 View Play Anmentioning
confidence: 99%
“…Self Identity: [29], have proposed the research about the social influencers. The authors have mentioned about social identity theory that our global society has various categories of social and social group.…”
Section: Literature Reviewmentioning
confidence: 99%